Assessment of Acute Toxicity of Quinazoline Derivative 3-[2-oxo-2-(4-Phenylpiperazine-1-yl)Ethyl]quinazoline-4(3h)-oh Active against Opportunistic Microorganisms - N. M. Gabitova; A. A. Tsibizova; A. A. Ozerov; M. A. Samotrueva (Антибиотики и Химиотерапия, 2023)
The study is devoted to the study of acute toxicity of a new quinazoline compound — 3-[2-Oxo-2-(4-phenylpiperazine-1-yl)ethyl]quinazoline-4(3H)-one (VMA-10-21), promising as an antimicrobial agent active against opportunistic microorganisms. Purpose. Assessment of acute toxicity of the quinazoline derivative 3-[2-oxo-2-(4-phenylpiperazine-1yl)ethyl] quinazoline-4(3h)-oh, exhibiting antimicrobial activity. Material and methods. All experiments were carried out on non-linear mature female rats with a body weight of 180–190 g. Female individuals were in the diestrus stage. The rats were divided into groups (n=6) by a random sample, there were 4 individuals in each group and were kept in cages for a week before the experiment, getting used to laboratory conditions: animals receiving intragastric equiobjection of distilled water (control); experimental animals treated with the compound VMA-10-21 at doses of 1000, 2000; 5000 mg/kg (the doses were selected based on the fact that the study of the toxicity of pyrimidine derivatives with a similar chemical structure showed their relative safety and the absence of lethality from a dose of 500 mg/kg). Results. Assessment of acute toxicity of the quinazoline derivative 3-[2-oxo-2-(4-phenylpiperazine-1yl)ethyl]quinazoline-4(3h)-oh with intragastric administration showed that this compound belongs to class 5 toxicity and is low-toxic according to. Under these conditions, and for LD₅₀, the maximum dose is 5000 mg/kg. However, despite the results obtained, when this compound was administered at a dose of 5000 mg/kg, changes in hemoglobin, the number of leukocytes and platelets, as well as total protein were observed, which may indicate the possible development of pathological changes in the hematopoietic and hepatobiliary systems. Conclusion. Thus, the quinazoline derivative 3-[2-oxo-2-(4-phenylpiperazine-1yl)ethyl]quinazoline-4(3h)-oh with intragastric administration is low-toxic and belongs to the 5th class of toxicity, and therefore the maximum dose is 5000 mg/kg for LD₅₀. However, given the fact that there are changes in hematological and biochemical parameters, this compound needs to be studied in detail under the conditions of course effects on the body of animals.